(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
This proposal arises in response to traditional methodologies used in school mathematics, common in this area and that make it unpleasant for students. With this work we want to contribute to the development of geometric and metric thinking, supported by forms of work that are attractive to students, such as physical education and dances. This proposal works on body movement, important at the age in which fifth grade students are, without losing the mathematical horizon and without distancing themselves from the referents of education in Colombia such as standards, curricular guidelines and the basic rights of learning. After applying these guides where body movement is the basis for learning geometry, the students’ learning and the disposition of work created by this methodology were evaluated. It is also an invitation to recover the teaching of geometry, very important in mathematics, but sometimes forgotten.